1989
DOI: 10.1007/bf00698853
|View full text |Cite
|
Sign up to set email alerts
|

A case of hemorrhagic pineal cyst: MR/CT correlation

Abstract: A 30-year-old male had a headache for one month and was evaluated with both computed tomography (CT) and magnetic resonance (MR). These scans demonstrated an obstructing pineal cyst containing layered acute and subacute blood products by MR criteria. The concurrent scans allowed correlation between CT and MR findings in this rare complication of an unusual entity, explained his headache (and the development of later upward gaze paresis), provided a precise surgical/anatomic approach, and gave a good final clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…Rarely, pineal cysts have been associated with gaze palsy or Parinaud syndrome. 11,17,29,36,39,40,46,47,67,69 We did not have any patients with either of these clinical manifestations in our series. The frequent association of other, likely incidental, symptoms with pineal cysts will make the clinical interpretation of any symptoms challenging.…”
Section: Discussionmentioning
confidence: 92%
“…Rarely, pineal cysts have been associated with gaze palsy or Parinaud syndrome. 11,17,29,36,39,40,46,47,67,69 We did not have any patients with either of these clinical manifestations in our series. The frequent association of other, likely incidental, symptoms with pineal cysts will make the clinical interpretation of any symptoms challenging.…”
Section: Discussionmentioning
confidence: 92%
“…5 Over the subsequent years, sporadic reports of large symptomatic pineal cysts causing headache, Parinaud's syndrome, long tract signs, and pineal apoplexy appeared in the literature. 10,11,17,19,20,25 Although rare cases of pineal cysts continued to be reported, in nearly all cases the determination of "symptomatic" relied on signs of ventriculomegaly or Parinaud's syndrome. Klein and Rubinstein reported that among a surgical series of 7 symptomatic pineal cysts ranging in size from 1.0 to 4.5 cm, 5 patients demonstrated improvement following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Other sporadic reports suggest that a pineal cyst may cause intermittent obstruction of the sylvian aqueduct or compression of critical neural structures, making resection a reasonable option. 7,13,15,[17][18][19][20][21]25,26 Noncommunicating hydrocephalus and Parinaud's syndrome are rarely caused by a simple pineal cyst. Therefore, the benefit of surgery in the absence of intracranial hypertension is unclear.…”
mentioning
confidence: 99%
“…With regard to the possible natural history/growth of pineal cysts, previously published reports that spanned periods of 3 months to 4 years did not show visible enlargement as determined by MR imaging [Tamaki et al, 19891. On the other hand, the potential for spontaneous rupture and collapse of pineal cysts was reported in two cases in one of these studies [Tamaki et al, 19891. Only occasionally do pineal cysts cause signs or symptoms. According to published reports, these clinical manifestations may include headache, diplopia, Parinaud's sign, nausea, vomiting, papilledema, dysarthria, and visual disturbances [Osborn et al, 1989;Musolino et al, 1993;Stern and Ross, 19931. However, by far the majority of pineal cysts cause no signs or symptoms and are believed to be incidental to any presenting clinical syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…As an aid in differentiating these other lesions from benign pineal cysts on the basis of MR imaging, dermoid cysts often contain a component of hyperintense fat, epidermoid lesions are usually larger and insinuate extensively into the surrounding cisterns, teratomas are often large and complex in their make-up with fat content and/or regions of solid enhancement after gadolinium administration, arachnoid cysts frequently exert a greater relative degree of mass effect and do not have an enhancing rim, and cysticercotic cysts on high resolution imaging often contain a visible mural scolex while at the same time showing other cysticercotic lesions elsewhere in the cranium. In addition, many of these latter pathologic processes are greater in size overall than most pineal cysts, have larger solid tissue component(s) and frequently present with obstructive hydrocephalus [Muller-Forell et al, 1988;Tamaki et al, 1989;Osborn et al, 1989;Tien et al, 1990;Zee et al, 199 11. Finally, pineal cell tumors do not usually undergo cystic degeneration at the relatively small size usually encountered in benign pineal cysts; and when tumoral cysts are present the ratio of solid tissue to cyst in neoplasia is typically greater [Muller-Forell et al, 1988;Tien et al, 1990;Zee et al, 19911. Calcifications are very common in the pineal gland, reaching an incidence as high at 84% as de-termined by histological investigation [Wildi and Frauchiger, 18651.…”
Section: Discussionmentioning
confidence: 99%